EVALUATION AND DEVELOPMENT OF THE MEAT INDUSTRY IN KAZAKHSTAN AND ABROAD - A. E. Kokеnova; G.I. Adbikerimova; D.A. Kulanova; A.Y. Yesbolova; A.T. Mergenbayeva (Scientific Journal of Pedagogy and Economics, 2021)
іn the meat balance of Kazakhstan, the defining place belongs to beef, which cannot be replaced by other types of meat, since each of them has specific taste qualities, amino acid composition and nutritional value. However, a sharp decline in the production of beef products of cattle breeding during the years of market transformations led to a significant reduction in the consumption of beef and veal by the population against the background of a decrease in the supply of domestic meat and a significant increase in its import supplies in frozen form, mainly from far-abroad countries. As a result of increased competition between producers of certain types of meat, beef producers were not in the best economic position. The functioning of the market of meat products of cattle breeding is complicated due to a sharp reduction in state support for the industry, the discrepancy in prices for meat products of cattle breeding and the material elements of the costs of its production, the violation of economic relations between economic entities of the market, the fall in the effective demand of the population. The urgency of solving the problem of the development of the domestic meat market increases due to the loss of Kazakhstan’s food security for this type of food. The purpose of the study was to develop theoretical, methodological and methodological provisions of recommendations for the development of the market of meat products of cattle breeding in Kazakhstan. The object of the study was agricultural producers and meat processing enterprises. In order to successfully compete in the domestic and foreign markets, agribusiness enterprises must ensure the production of competitive products, which is associated with one of the economic problems of the processing industries of the agro-industrial complex, which also includes the meat processing subcomplex. The scientific novelty is as follows: the theoretical foundations of the functioning of the market of meat and meat products as a complex and dynamically developing multifunctional production and economic system are revealed.